2022
DOI: 10.1212/cpj.0000000000200065
|View full text |Cite
|
Sign up to set email alerts
|

Area Postrema Syndrome

Abstract: Abstract:Objectives:Area postrema syndrome (APS) is one of the core clinical feature of neuromyelitis optic spectrum disorder (NMOSD). APS is mostly associated with neuromyelitis optica (NMO) and rarely reported in myelin oligodendrocyte glycoprotein antibody disease (MOGAD). We herein report a case of area postrema syndrome as the initial presentation of double seropositive aquaporin-4 (AQP-4) and myelin oligodendrocyte glycoprotein (MOG)antibody.Methods:The patient fulfilled the NMOSD diagnostic criteria. MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…No gastrointestinal disease was identified by the gastroenterologist for any patients. APS at onset especially when when it occurs independently might delay the diagnosis of NMOSD and cause further neurological deficits in the form of ON, transverse myelitis, or brainstem syndrome [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No gastrointestinal disease was identified by the gastroenterologist for any patients. APS at onset especially when when it occurs independently might delay the diagnosis of NMOSD and cause further neurological deficits in the form of ON, transverse myelitis, or brainstem syndrome [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case report, the final diagnosis was MOGAD [ 9 ]. Abhay et al reported a case of APS as the initial presentation of double-seropositive aquaporin-4 and myelin oligodendrocyte glycoprotein (MOG) antibodies [ 10 ]. However, owing to its low frequency in MOGAD, data on APS involvement in MOGAD are limited to subsets of case series, and only a few studies have focused on APS in MOGAD [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the AP, SFO, and OVLT have fenestrated capillaries and are characterized by high blood-brain barrier permeability and thus are easily reachable by the SARS-CoV-2 virus via the bloodstream. Moreover, the AP has been associated clinically with the AP syndrome (characterized by intractable nausea, vomiting and hiccups for at least 48 hours) (eg, 47 ), which is also one of the core clinical features of neuromyelitis optica spectrum disorder (NMOSD). Neuromyelitis optica spectrum disorder is considered an autoimmune disease in which antibodies (ie, aquaporin-4-IgG or anti-AQP4 antibodies) are produced against the water channel protein aquaporin-4 (AQP4) present in perivascular astrocytes 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…3), to our knowledge, only the AP has been detected for clinical purposes to date. 65 There have been a few recent clinical reports showing alterations of the AP in patients affected by AP syndrome 47,65 and NMOSD including AP syndrome as the initial symptom. 65 Nevertheless, the latter investigation 65 did not address whether SFO or OVLT alterations were present as well.…”
Section: Can Neuroimaging Help Us Detect Sfo and Ovlt Pathology?mentioning
confidence: 99%